International Policy and Roma Education in Europe: Essential Inputs or Centralized Distractions? - Ram, Melanie H. (Alberta Journal of Educational Research, 2016)
This article examines the case of Roma inclusion in education as a study of the ways in which international policy can and cannot bring change at the local level. I first reflect on the numerous international organizations and initiatives to improve the educational outcomes of Roma, and to reduce segregation and other non-inclusionary practices. Given these actions—and their relatively small impact—I identify both benefits and drawbacks of international efforts to achieve Roma inclusion and improve education outcomes. I conclude that international organizations provide significant inputs for Roma inclusion, but also serve as centralized distractions that foster extremely high expectations and thus great disappointment with the results. Cet article examine le cas de l’inclusion des Roms dans le système éducatif comme moyen d’évaluer la mesure dans laquelle la politique internationale peut effectuer des changements à l’échelle locale. Ma réflexion porte d’abord sur les nombreux organismes internationaux et les multiples initiatives qui visent l’amélioration de l’éducation aux Roms, et la réduction de la ségrégation et autres pratiques non-inclusives. Compte tenu de ces démarches—et de leur impact relativement petit—j’identifie tant les bienfaits que les désavantages des efforts internationaux qui essaient d’augmenter l’inclusion des Roms et améliorer leur éducation. Je conclus que les organismes internationaux contribuent de façon considérable à l’inclusion des Roms, mais qu’ils servent également de distractions centralisées qui favorisent des attentes extrêmement élevées et ainsi, une grande déception quant aux résultats.